Cancer of the testis, socioeconomic status, and occupation. - Swerdlow, A J (1991)
The risk of testicular cancer in relation to lifetime histories of socioeconomic status, occupation, and occupational exposures was examined in a case-control study in England. Interviews were conducted with 259 cases, 238 control patients treated at radiotherapy and oncology centres, and 251 controls who were hospital inpatients in other departments. Risk of testicular cancer was raised in men of high socioeconomic status measured both by occupation and in other ways, and was similar in relation to status measured at birth and at various later stages of life. The occupations with highest risk of the tumour were paper and printing workers, professionals, and administrators. Exposures to various specific occupational agents that have been suggested in publications as potential risk factors were examined, but none showed an association with risk. The relative risk for occupational exposure to ionising radiation was 1.62 (95% confidence interval 0.83-3.17).